A leaner, meaner lifeline: How supply chain efficiency boosts the performance of humanitarian aid in Kenya - Erastus Kiswili Nyile (Journal of Sustainable Development of Transport and Logistics)
Purpose: This study examines how supply chain efficiency influences the performance of humanitarian aid organizations in Kenya, focusing on the moderating role of organizational characteristics such as size, age, and structure. Methodology: A mixed-methods approach was employed, combining quantitative data from a census survey of 330 humanitarian organizations with qualitative insights from supply chain managers. Data were analyzed using descriptive statistics, regression analysis, and thematic content analysis to assess supply chain efficiency's direct and moderated effects on organizational performance. Results: Findings reveal that supply chain efficiency significantly impacts the performance of humanitarian aid organizations (β=0.547, p<0.05), accounting for 43.6% of the variance in performance. When organizational characteristics are included, the explanatory power increases to 66.5%. Qualitative analysis highlights that waste elimination, cost optimization, and robust internal controls are critical for improving efficiency. Corruption and diversion of resources were identified as key forms of waste, while mechanisms such as audits and checks and balances effectively mitigate these issues. Theoretical Contribution: The study extends the Theory of Constraints to the humanitarian context, demonstrating that addressing organizational bottlenecks and inefficiencies can substantially enhance aid delivery outcomes. It also integrates lean supply chain principles into the unique challenges of humanitarian logistics. Practical Implications: The results underscore the importance of adopting lean management practices, investing in modern supply chain technologies, and tailoring supply chain strategies to organizational characteristics. These actions can enhance responsiveness, accountability, and resource utilization, ultimately improving the impact of humanitarian operations in crisis settings.